The OO : Drawings 2000 at Barbara Gladstone Gallery. - Kertess, Klaus (New York : Barbara Gladstone Gallery, 2000)
Acconci Studio ; Althoff, Kai ; Artschwager, Richard ; Baldessari, John ; Balka, Miroslaw ; Balkenhol, Stephan ; Barney, Matthew ; Bechtle, Robert ; Berkenblit, Ellen ; Blake, Nayland ; Bleckner, Ross ; Bock, John ; Bourgeois, Louise ; Brown, Cecily ; Celmins, Vija ; Chilver, John ; Clemente, Francesco ; Condo, George ; Craig-Martin, Michael ; Currin, John ; Doig, Peter ; Dowell, Roy ; Dumas, Marlene ; Dunham, Carroll ; Durant, Sam ; Dzama, Marcel ; Edmier, Keith ; Fairhurst, Angus ; Feinstein, Rachel ; Fischl, Eric ; Gardner, Tim ; Gornik, April ; Grotjahn, Mark ; Hanson, Chris ; Herrera, Arturo ; Hopton, Georgie ; Horn, Roni ; Hume, Gary ; Innes, Callum ; Joo, Michael ; Kabakov, Ilya ; Kaplowitz, Jane ; Kapoor, Anish ; Katz, Alex ; Kelly, Ellsworth ; Kilimnik, Karen ; Kusama Yayoi ; Landers, Sean ; Larner, Liz ; Le Va, Barry ; Lethbridge, Julian ; LeWitt, Sol ; Manders, Mark ; Mangold, Robert ; Marden, Brice ; McCarthy, Paul ; Moffett, Donald ; Morrison, Paul ; Mullican, Matt ; Muntean & Rosenblum ; Murakami, Takashi ; Murray, Elizabeth ; Nara, Yoshimoto ; Neto, Ernesto ; Nicolai, Carsten ; Ofili, Chris ; Oursler, Tony ; Owens, Laura ; Pettibon, Raymond ; Peyton, Elizabeth ; Phelan, Ellen ; Phillips, Richard ; Pierson, Jack ; Pittman, Lari ; Prince, Richard ; Raho, Allessandro ; Ray, Charles ; Ritchie, Matthew ; Rockman, Alexis ; Ross, Alexander ; Saccoccio, Jackie ; Salle, David ; Sarmento, Julião ; Saul, Peter ; Scheibitz, Thomas ; Schimert, Katy ; Schneider, Gregor ; Schumann, Christian ; Segre, Michelle ; Serra, Richard ; Serse ; Shapiro, Joel ; Sietsema, Paul ; Sikander, Shahzia ; Skreber, Dirk ; Smith, Kiki ; Sonnenberg, Hendrika ; Spalletti, Ettore ; Stark, Frances ; Sullivan, Billy ; Taaffe, Philip ; Tàpies, Antoni ; Therrien, Robert ; etc.
Engels
OO : Drawings 2000 at Barbara Gladstone Gallery, Barbara Gladstone Gallery, New York, 6 July - August 2000
boek